The Strategy of the Head of Madrasah in Cultivating Fastabiqul Khoirot Culture in the State High School Environment in Batu City - Hasan Assidiqi, ali; Jazuli, Ahmad; Yusuf Salsabila, Adi; Dini Sadiyah (Universitas Nahdatul Ulama Surabaya, 2023)
Good culture in Islam is often called fastabiqul khoirot which means competing or competing for good. This kind of culture must be owned by everyone including in an institution if they want their institution to develop well. This study aims to describe the steps or strategies of the Head of Madrasah to stimulate or awaken Fastabiqul Khoirot culture and analyze several factors in its application. The research method uses Descriptive-Qualitative studies. Data collection using observation, interview and documentation methods. The object of research is at MAN Batu City. Results found: 1) The strategy of the Head of Madrasah includes: Divide clear tasks for each element, respect every constructive opinion or proposal from each element, reward every achievement achieved, and build a winning mentality and unyielding attitude. 2) The analysis from the Head of Madrasah about the factors that become obstacles and solutions include: Newly recruited teachers and education staff have not been able to carry out jobdis optimally, so the school must provide assistance, all elements on average are still shy in submitting an idea or proposal about school development, the solution is that the Head of Madrasah approaches with a persuasive approach, there is still envy between members to continue to compete, There is no effective solution, and constrained by the assumption that the task is a burden that results in discouragement if the task is not successfully done, the solution builds motivation with direction and example to change someone's main said about it.